Comparative Analysis for Prediction of Rainfall using Data Mining Techniques with Artificial Neural Network - Sukanya, R; Prabha, K (International Journal of Computer Sciences and Engineering, 2025)
Rainfall Prediction is essential for countries which are based on agricultural economy like India. There are several factors are used to predict the rainfall such as temperature, pressure, wind speed, humidity, Mean sea-level etc. The accurate Rainfall Prediction is one of the most challenging problems in the atmospheric research. This paper discuss about Data mining technique which is suitable to predict the rainfall. This was carried out using several Classification algorithms such as Decision tree and Artificial Neural Network. ANN is a non-linear data modelling tool which is used to enhance the capability of Data Mining. It provides high accuracy, flexibility, good robustness, distributed storage and parallel processing. In this paper Back propagation Neural Network, Support Vector Machine is used for rainfall prediction. ANN improves the efficiency of Rainfall prediction by analysing the historical and current facts to make accurate predictions about future. For rainfall prediction, several Data mining techniques are used with ANN and comparison has been done by many researches are discussed.